PEMBELAJARAN BERBASIS LINGKUNGAN DALAM PERSPEKTIF LINGKUNGAN BELAJAR - Mukhlishi, Mukhlishi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
Environmental-based education is a key determinant and factor in building children's abilities and behaviors, the environment occupies an important position, therefore the implication is the provision of a conducive environment both indoor and outdoor. It must be supported by environmental health that becomes an integral part for learners to be able to learn and improve their cognitive, motor and affective ability becomes a must in an educational institution. So pekembangan the world of education always want to give different nuances and accompanied by the output quality of educational institutions itself which essentially creates a disciplined learning conditions and must be supported by health that becomes part of the determinant of conducive learning conditions.